Tuning SERS properties of pattern-based MWNTs-AuNPs substrates by adjustment of the pattern spacings. (September 2018) - Mei, Hui; Zhao, Xing; Bai, Shenwei; Li, Qingwen; Xia, Junchao; Bai, Haili; Cheng, Laifei
Abstract: Vertically-aligned multi-walled carbon nanotubes (MWNTs) arrays were designed with different pattern spacings on silicon wafer and tunable three-dimensional (3D) surface-enhanced Raman scattering (SERS) substrates were fabricated by decorating the patterned MWNTs arrays with gold nanoparticles (AuNPs) via magnetron sputtering and annealing. SERS substrates with large amounts of "hot spots" were achieved by adjusting the thickness of sputtered gold film. The microstructure of MWNTs-AuNPs hybrid materials were examined under scanning electron microscopy (SEM) and transmission electron microscope (TEM). The Raman scattering behavior of MWNTs arrays was systematically investigated. Surface-enhanced Raman scattering property of MWNTs-AuNPs was demonstrated using molecular probes Rhodamine 6G (R6G) solutions as standard analyte and the pattern spacing was found to significantly affect Raman intensity. MWNTs-AuNPs substrates with pattern spacing of 100 nm were used to evaluate the SERS property of the material and the detection concentration level was found as low as 10 −10  M. Graphical abstract: Image